Multifunctional Conductive Nanofibers for Self‐Powered Glucose Biosensors - Seda Gungordu Er; Rameesh Bulathsinghala; Selvinaz Burcu Kizilates; Bing Li; Rucchi Ryan; Tanveer A. Tabish; Ishara Dharmasena; Mohan Edirisinghe (Advanced Science)
Abstract Electrochemical glucose biosensors are essential for diabetes management, and self‐powered systems present an eco‐friendly and innovative alternative. Traditional biosensors face several limitations including limited sensitivity, enzyme instability, and dependency on external power sources. Addressing these issues, the study develops a novel multifunctional nanofiber integrating biosensor for glucose detection and a self‐powered motion sensor, utilizing an innovative triboelectric nanogenerator (TENG) system. Electrospun nanofibers, composed of graphene oxide (GO), porous graphene (PG), graphene foam (GF), polypyrrole (PPy), and polycaprolactone (PCL), demonstrate enhanced electrical conductivity, triboelectric efficiency, and mechanical strength. Among these, dip‐coated nanofibers exhibited the highest conductivity of 4.9 × 10⁻⁵ S/cm, attributed to superior surface electrical properties of GO. PCL/PPy/GO nanofibers achieved the highest glucose detection performance in cyclic voltammetry and differential pulse voltammetry due to efficient electron transfer mechanisms of GO and PPy. Additionally, triboelectric tests revealed peak voltages of 63V with PCL/PPy/GO and polyvinylidene fluoride nanofibers containing glucose oxidase enzyme. Core‐sheath and dip‐coated nanofibers also demonstrated significant mechanical resilience (∼0.9 N force, ∼350 s durability). These findings highlight PCL/PPy/GO nanofibers as a multifunctional, efficient, and scalable solution, offering highly sensitive glucose detection and non‐invasive sweat analysis along with robust energy harvesting for environmentally friendly and advanced diabetes management systems.